Gender Capability of Elected Offi cials and Civic Leaders in Public Speaking - Arong, Cecilia D. (JPAIR Multidisciplinary Research, 2012)
In Southern Leyte, thousands of elected/appointed male/female village officials and civic leaders give public speeches. Very few of them receive training in public speaking. Culture claims that male officials are better than female in decision making, running the village, leading an organization, setting disputes and giving public speeches as the father's decision in the family is final and his word is firm and executor. This study compares the speaking abilities of male and female village officials/civic leaders as to: manner of presenting speeches, self-confidence; thought organization, voice quality, eloquence, and audience impact. Officials/leaders of Sogod villages are trained in Public Speaking for ten consecutive Sundays at Mahayahay Public Stage. After every lecture, participants' speeches followed. During the culmination, every participant presented a public speech composed of opening remarks, welcome address, inspirational talk, closing remarks, introduction of guest speaker, interviewing, panel discussion, broadcast speech, necrological services and campaign speeches rated by three judges using pre-established criteria. Mann-Whitney Test, non-parametric test, used ordinal data to compare the male and female abilities in public speaking. Significant results showed that male and female officials have comparable manners of presenting speeches, self-confidence, thought organization, eloquence, voice quality, and audience impact.
Keywords: public speaking; village official; inspirational talk